Implementasi Metode Qira’ati Dalam Meningkatkan Bacaan Al Qur’an Melalui Kegiatan Ekstrakurikuler di MTs. Tarbiyatul Wathon - Nashihin , Muhammad (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
In learning the Al Qur'an Hadith subject which was carried out at MTs. Tarbiyatul Wathon has obstacles, namely the presence of several students, especially new students who are not fluent in reading the Qur'an and become obstacles for teachers of the Al-Qur'an Hadith subject to carry out teaching assignments, from these obstacles in the end extracurricular activities are made in the form of intensive activities read the Qur'an by applying the Qira'ati method, the purpose of this study is to overcome these obstacles by using a qualitative approach. This research is categorized as field research, namely research conducted directly in the field to obtain the necessary qualitative data in the form of observations, interviews, and documentation. With the implementation of the Qira'ati Method to increase Al Qur'an reading through extracurricular activities at MTs. Tarbiyatul Wathon Campurejo Panceng Gresik has a positive impact on learning Al Qur'an Wa Al Hadith Subject which can be concluded as follows: Teachers experience ease in teaching especially Subject Teachers of Al Qur'an Wa Al Hadith, and generally Subject Teachers of Islamic Religious Education , Students easily understand the subject matter provided by the teacher because they can already read the Qur'an and Hadith properly as a basis that must be mastered by all students, and it is easier for institutions to make reports of learning completeness in the curriculum to be reported to supervisors and agencies that oversee them which can be seen in the student report book.